Lunge as a sport-specific exercise: A mini review - Nadzalan, A. M.; Hannan Sazali, M.; Shahrul Azzfar, M. (Journal of Engineering and Science Research, 2018)
As a way to enhance performance in sports, apart from in-field or in court training, athletes are recommended to adopt resistance training into their training routine. As an exercise that needs the performer to split their legs, lunge is suggested to be included as an exercise in a training session. Various researches had been conducted on lunge and several findings showed different methods or protocols of lunge affect the kinematics, kinetics muscle activation and fascicle behaviour response during the exercise. Although not much study conducted on the chronic adaptations, the existing studies suggested